Histopathologic features of an autopsied patient with cerebral small vessel disease and a heterozygous HTRA1 mutation. Issue 4 (25th May 2018) - Ito, Junko; Nozaki, Hiroaki; Toyoshima, Yasuko; Abe, Takashi; Sato, Aki; Hashidate, Hideki; Igarashi, Shuichi; Onodera, Osamu; Takahashi, Hitoshi; Kakita, Akiyoshi
Abstract : Cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL) is a hereditary cerebral small vessel disease (CSVD) caused by homozygous or compound heterozygous mutations of the high temperature requirement A serine peptidase 1 gene ( HTRA1 ). Affected patients suffer from cognitive impairment, recurrent strokes, lumbago and alopecia. Recently, clinical studies have indicated that some patients with heterozygous mutations in HTRA1 may also suffer CSVD. Here, we report the histopathologic features of an autopsied 55‐year‐old male patient who had shown cognitive impairment and multiple cerebral infarcts, and was found to have a heterozygous missense mutation (p.R302Q) in the HTRA1 gene. Histologically, small vessels in the brain and spinal cord showed intimal proliferation, splitting of the internal elastic lamina, and degeneration of smooth muscle cells in the tunica media. Thus, although less severe, the features were quite similar to those of patients with CARASIL, indicating that patients with heterozygous mutations develop CSVD through underlying pathomechanisms similar to those of CARASIL.